2005
DOI: 10.1007/s11249-004-1766-7
|View full text |Cite
|
Sign up to set email alerts
|

Wear resistant solid lubricant coating made from PTFE and epoxy

Abstract: A composite coating of polytetrafluoroethylene and epoxy shows 100 · improvements in wear resistance as compared to either of its constituents alone and reduced friction coefficient under testing on a pin-on-disk tribometer. This coating is made by impregnating an expanded PTFE film with epoxy, which provides three unique functions: (1) the epoxy compartmentalizes the PTFE nodes, which is believed to reduce the wear of the PTFE, (2) the epoxy increases the mechanical properties such as elastic modulus and hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 24 publications
1
48
1
Order By: Relevance
“…They found transfer films in the lowest wear system were~30% harder and stiffer than either counterpart material and suggested that this was the result of mechanical alloying. McCook et al [56] conducted similar measurements on the wear surface of a PTFE-epoxy composite. Whereas the composite contained clear regions of high and low hardness from the epoxy and PTFE, respectively, the wear surface exhibited uniformly low hardness, suggesting that a running film of PTFE was preferentially drawn over the entire surface; these PTFE running films were thought to substantially decrease friction and wear by preventing adhesion between the epoxy phase and the counterbody.…”
Section: Mechanical Properties Of the Transfer Filmmentioning
confidence: 97%
“…They found transfer films in the lowest wear system were~30% harder and stiffer than either counterpart material and suggested that this was the result of mechanical alloying. McCook et al [56] conducted similar measurements on the wear surface of a PTFE-epoxy composite. Whereas the composite contained clear regions of high and low hardness from the epoxy and PTFE, respectively, the wear surface exhibited uniformly low hardness, suggesting that a running film of PTFE was preferentially drawn over the entire surface; these PTFE running films were thought to substantially decrease friction and wear by preventing adhesion between the epoxy phase and the counterbody.…”
Section: Mechanical Properties Of the Transfer Filmmentioning
confidence: 97%
“…composite was machined from a sample that was prepared via a powder blending and compression molding procedure described in [6], and the ePTFE/epoxy coatings were prepared as described in [7]. The PTFE/PEEK composite was 50 wt% PEEK and the ePTFE/epoxy composite was 46 wt% epoxy.…”
Section: Authormentioning
confidence: 99%
“…There were two objectives for this research effort. This first objective was to collect data on PTFE, a PTFE/PEEK composite [6], and an expanded PTFE/ epoxy coating (table 2) [7] from ambient temperatures to cryogenic temperatures in an inert gaseous environment of high purity nitrogen (<5PPM O 2 and H 2 O). The second objective was to link the frictional behavior at cryogenic temperature to the existing data and models for the frictional behavior at ambient temperatures and above.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it particularly challenging to develop tribological coatings that work equally well in terrestrial and space environments. Multifunctional materials are being explored for use in such coatings; nanostructured polymer composites have been shown to be particularly good candidates, especially those that include polytetrafluoroethylene (PTFE) [1][2][3]. The C-F bond in PTFE provides both thermal and oxidative stability, and confers resistance to almost all solvents [4].…”
Section: Introductionmentioning
confidence: 99%